Toxic Alcohol Ingestion/Methanol Ingestion - Mary Wittler; Mary Claire O'Brien; David A. Masneri (Association of American Medical Colleges, 2018)
Introduction Methanol poisoning is an uncommon life-threatening ingestion associated with significant morbidity and requires prompt diagnosis and management for the best possible outcome. We created a simulation case that challenges learners to analyze case information, construct a differential diagnosis of an anion gap metabolic acidosis, narrow the differential based on reasoning, and empirically initiate management. Methods The simulation case was designed for emergency medicine residents and pediatric emergency medicine fellows. The activity began with a brief overview of the monitors, equipment, and simulation experience. First-year residents managed the case as a team of two. Second- and third-year residents and fellows managed the case alone. The learners had 15 minutes to complete a focused history and physical exam, request and interpret labs and studies, provide stabilization of life threats, and initiate specific interventions based on a presumptive diagnosis. The simulation was followed by a 20-minute facilitated debrief session that reviewed key learning points and learner performance based on an evaluation checklist. Results Residents completed a six-question, 5-point Likert-scale postparticipation questionnaire. Overall, residents reported a high degree of satisfaction with the simulation experience. The case and debrief were effective in meeting the educational objectives and proved to be an effective modality to fill this educational gap. Discussion This simulation experience successfully exposed residents to the uncommon presentation of methanol poisoning. The simulation experience effectively closed the identified educational gap and provided an experiential learning opportunity that accomplished the targeted learning objectives.